My Ántonia - Cather, Willa, 1873-1947 (Open Road Integrated Media, 2016)
The moving story of one woman's struggles and triumphs on the Nebraska frontier In the breathtaking final volume of her acclaimed Prairie Trilogy, Pulitzer Prize-winning novelist Willa Cather brings to life one of the most remarkable heroines in American literature. The eldest daughter of Bohemian emigrants, fourteen-year-old Ántonia Shimerda arrives in Black Hawk, Nebraska, blissfully unaware of the poverty and heartbreak that lie in store for her family. But as one calamity after another befalls the Shimerdas, Ántonia finds the strength not merely to survive, but to thrive. Under the watchful eye of Jim Burden, her neighbor and childhood friend, Ántonia blossoms into a woman as beautiful, captivating, and resilient as the Great Plains. Told in lush and evocative prose, My Ántonia is a masterpiece of twentieth-century literature and a stirring tribute to the homesteaders whose pioneer spirit tamed the American West. My Ántonia is the 3rd book in the Prairie Trilogy, but you may enjoy reading the series in any order. This ebook has been professionally proofread to ensure accuracy and readability on all devices.